Evaluasi Fraud Risk akibat Lemahnya Sistem Pencatatan Keuangan pada Usaha Kedai Kopi L.K Kota Malang - Salsabila, Aqila; Prajawati, Maretha Ika (Maliki Interdisciplinary Journal, 2026)
This study aims to evaluate the fraud risk arising from weak financial recording systems at Kedai Kopi L.K in Malang City. Small businesses such as coffee shops often operate with simple procedures and without structured recording systems, which creates potential opportunities for fraud to occur. Using a qualitative approach with a case study method, this research collects data through observation and interviews to identify how the Fraud Triangle Theory—comprising pressure, opportunity, and rationalization—contributes to the emergence of fraud. The findings show that “opportunity” is the dominant factor due to weak supervision, lack of task separation, the use of unofficial cashier applications, and the absence of supporting documentation in transaction recording. Rationalization also appears as the perpetrator attempts to justify the fraudulent actions committed. Meanwhile, pressure is found to be the weakest factor influencing the fraud behavior. These conditions indicate poor internal control quality within the financial system of Kedai Kopi L.K. This study highlights the importance of implementing Internal Control Quality (ICQ) and utilizing the COSO framework as a strategy to mitigate fraud risk for micro, small, and medium enterprises, particularly in the culinary sector.